Muslim Parents' Ways in Providing Sex Education and Guidance for Teenagers - Desya safitri; Siti Hulaiyah (Counselle| Journal of Islamic Guidance and Counseling, 2021)
This article aims to provide a pattern of understanding to Muslim Parents that sex education guidance is very necessary for teenagers. By providing understanding and guidance on sex education in the context of Islam, it is hoped that adolescents can grow into young people who believe and fear Allah SWT, and can maintain their own chastity. The type of research used is the descriptive qualitative method, the data comes from a questionnaire survey of Muslim Parents with 46 respondents. The results of this study indicate that there are still many parents who feel foreign and taboo about adolescent sex education. Parents consider sex education to be done as adults and told by teachers at school.